TINDAK TUTUR ILOKUSI DALAM LIRIK LAGU ALBUM AKU WANITA BIASA KARYA KRISDAYANTI - nida, sofiyatun (Universitas Tidar, 2022)
This study aims to describe the forms of ilocutionary speech act classification in the lyrics of the song Aku Wanita Biasa album by Krisdayanti. The data source in this study is the sing lyrics in the I’m an Ordinary Woman Album by Krisdayanti which consists of 12 songs: I’m an Ordinary Woman, Don’t Let Love Cry, I Can’t, Choose Me, Love You, The More I Love, Counting The Days, Never Regret, The Moon, Fragile, Stricken by Love, and The Power of Love. Thia research uses a theoretical approach, which is a pragmatic approach. The method use in this research is descriptive qualitative. The technique used in this study is refer to and note. The results of the study showed that there were 37 data included in the action of the ilocuti speech. Ilocutionary speech acts include (1) assertive, (2) directive, (3) commisive, and (4) expressive.